1981
DOI: 10.1172/jci110282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peritubular protein on solute absorption in the rabbit proximal tubule. A specific effect on NaCl transport.

Abstract: A B S T R A C T The effect of removal of peritubular protein on the reabsorption ofvarious solutes and water was examined in isolated rabbit proximal convoluted tubules (PCT) perfused in vitro. In 22 PCT perfused with ultrafiltrate (UF) and bathed in serum, volume absorption (JV) was 1.44 nl/mm per min and potential difference (PD) was -3.6 mV. When these same PCT were bathed in a protein-free UF, JV was reduced 38% without a change in PD. Simultaneous measurements of total CO2 net flux (JTCO2) and glucose eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 47 publications
(73 reference statements)
6
27
0
Order By: Relevance
“…Thus, it is quite possible that, although paraceilular permeability was unchanged, the cellular entry step could be affected by VE in a way so as to reduce Na entry into the cell leading to an apparem reduction in pump activity itself as measured by Ac^a-The results presented here do, however, prove that paracellular permeability changes through increased backleak do not account for the reduction in measured Na transport with HTF under our volume-expanded conditions. Similar lack of change in measured (Imai and Kokko, 1972) and indirectly derived (Berry and Cogan, 1981) P^^, was found in the rabbit isolated tubule on removal of albumin from the bath as a model for volume expansion. Those authors argued that because, under net volume flux conditions (1 -* b), net flux is only a small proportion of b -* 1 backflux, small but unmeasurable changes in Pfsj^ (reflecting paracellular backflux) could still account for the reduced net Na transport they found.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Thus, it is quite possible that, although paraceilular permeability was unchanged, the cellular entry step could be affected by VE in a way so as to reduce Na entry into the cell leading to an apparem reduction in pump activity itself as measured by Ac^a-The results presented here do, however, prove that paracellular permeability changes through increased backleak do not account for the reduction in measured Na transport with HTF under our volume-expanded conditions. Similar lack of change in measured (Imai and Kokko, 1972) and indirectly derived (Berry and Cogan, 1981) P^^, was found in the rabbit isolated tubule on removal of albumin from the bath as a model for volume expansion. Those authors argued that because, under net volume flux conditions (1 -* b), net flux is only a small proportion of b -* 1 backflux, small but unmeasurable changes in Pfsj^ (reflecting paracellular backflux) could still account for the reduced net Na transport they found.…”
Section: Resultssupporting
confidence: 70%
“…In the rabbit in vitro isolated tubule preparation reducing bath protein concentrations, a model frequently equated with volume expansion experiments, did not result in a change of transepithelial p.d. although both Na and volume fluxes were decreased (Berry and Cogan, 1981;Imai and Kokko, 1972). Allhough we did not measure transepithelial p.d.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These authors therefore postulated that the decreased fractional bicarbonate reabsorption seen in volume-expanded states was related to changes in filtered load rather than to changes in peritubular protein concentration. In agreement with this proposal, Berry and Cogan using the isolated perfused rabbit PCT, found that bath protein removal did not inhibit bicarbonate absorption despite a significant depression in NaCl and volume absorption (18).…”
Section: Resultssupporting
confidence: 61%